COVID-19 vaccine therapeutic trials review: published results and registered protocols - Molka Osman; Mouna Safer; Aicha Hechaichi; Hejer Letaief; Sonia Dhaouadi; Chahida Harizi; Hamida Ben Salah; Sondes Derouiche; Leila Bouabid; Souha Bougatef; Nissaf Ben Alaya Bouafif (Journal of Global Health Reports, 2022)
# Background Since the emerging of Coronavirus disease 2019 (COVID-19) in late 2019 and the World Health Organization (WHO) declaring it as a pandemic, a race to develop a vaccine against COVID-19 has started worldwide and therefore huge efforts and resources have been put into achieving it. This review summarizes COVID-19 vaccines in phase III and IV.